Optimalisasi Potensi Pariwisata Daerah dengan Penguatan Aturan Daerah tentang Desa Wisata di Kabupaten Lamongan - Dymas Yulia Putri Kusumaningtyas; Akhmad Sirojudin Munir (Al-Maqashid: Journal of Economics and Islamic Business, 2022)
The background of the Lamongan Regency area which has tourism potential in the natural sector (marine, limestone mountains, and forestry), religion, culture and its location which is a downstream area of ​​three (3) major rivers in Indonesia makes it one of the tourist destinations in East Java province. This economic potential is in tandem with potential problems that arise (excessive reclamation, spatial planning violations, etc.) so that Lamongan Regency regional regulations are needed, so that their use can be felt in a sustainable manner, especially the strengthening of the smallest government in Indonesia, the Village Government, with the allocation of village funds that are comes from the APBN (State Revenue and Expenditure Budget). The number of tourism objects in rural areas that have become village icons or referred to as tourist villages without any regional regulations in the Lamongan district, makes the function and implementation less than optimal. The author uses a normative juridical approach to examine the legal rules related to tourism villages, both regarding the principles, objectives and functions of tourism, strategic goals, determination, submission, partnership and supervision.